What are skills? Some fundamental reflections - Tønnessen, Finn Egil (L1-Educational Studies in Language and Literature, 2012)
When the concept of ‘skill' is used in reading and writing research or more generally in linguistic research, it is rarely made the subject of detailed and precise definitions or reflections. The present article is a theoretical contribution that consists mainly in reflections on the type of phenomenon that ‘skill' represents. Philosophically, the account is based above all on Aristotle's views, according to which ‘skill' is characterised as a potentiality. Psychologically, this article expresses the opinion that the only way to describe, understand and explain ‘skill' is by combining behaviourism and cognitivism.